Impact of Sawmill Activities on Ambient Air Quality of Udu Area of Delta State, Nigeria - Edjere, Oghenekohwiroro; Mene-Enaike, Elohor; Asibor, Godwin; Bassey, Uwem (European Journal of Applied Sciences, 2025)
This study was set out to assess the impact of sawmill activities on ambient air quality in Udu Area of Delta State, Nigeria. The findings was achieved by monitoring and quantification of Nitrogen oxides (NOX), Volatile Organic Compounds (VOC), Sulphur Oxides (SOX), Carbon monoxide (CO), Suspended Particulate Matter (PM), Wind Speed and Wind Direction in and around settlements close to the Udu river during wet and dry season. The air quality status of the sampled areas was analyzed using Aero Qual series 500, MetOne Inst. (Aerocet 531S). Concentrations of pollutants analyzed were in the ranges for wet season; PM2.5 (15.80-74.0 µg/m3), PM10 (37.90-103.4µg/m3). Other results in (ppm) CO (0.01-0.47), CO2 (322-435.40). Dry season; (20.08-92.6 µg/m3) for PM2.5, PM10 (43.96-133.08µg/m3). Other results in (ppm) CO (0.01-0.78), CO2 (353-559.40). The air quality Index (AQI) ratings of the obtained results showed rating from Good to unhealthy for wet season and Good , moderate and unhealthy for dry season. There is need for a routine monitoring of the air quality in the study area to ensure safe.